ON THE MAIN FACTORS OF THE ESTABLISHMENT OF THE FIRST STATES (ON THE CASE OF CENTRAL ASIA) - Ulugbek Kholtojievich Shopulatov (Scholar Express Journals, 2021)
The article examines the conditions for the emergence of a state in Central Asia. Particular attention is paid to the role of production in the emergence of states and the importance of the growth of social relations with the advent of irrigation
Keywords: Irrigation; state; products; springs